2020
DOI: 10.1017/s0007114520004493
|View full text |Cite
|
Sign up to set email alerts
|

Dietary muramidase degrades bacterial peptidoglycan to NOD-activating muramyl dipeptides and reduces duodenal inflammation in broiler chickens

Abstract: Muramidases constitute a superfamily of enzymes that hydrolyze peptidoglycan (PGN) from bacterial cell walls. Recently, a fungal muramidase derived from Acremonium (A.) alcalophilum has been shown to increase broiler performance when added as a feed additive. However, the underlying mechanisms of action are not yet identified. Here we investigated the hypothesis that this muramidase can cleave PGN to muramyl dipeptide (MDP), activating nucleotide-binding oligomerization domain-containing protein 2 (NOD2) recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It has been shown that dietary muramidase has positive effects on chickens [ 10 ], rabbits [ 11 ], and pigs [ 12 , 13 ], which are largely due to the alteration in the gastrointestinal microbiota [ 14 ]. Muramidases also have immunomodulatory functions that have been established in livestock [ 15 , 16 ]. MUR hydrolyzes PGN-containing bacteria cell debris, which can improve digestive and absorptive functions and positive alteration of the intestinal inflammatory response, with subsequent enhancements in gut health and broiler performance [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dietary muramidase has positive effects on chickens [ 10 ], rabbits [ 11 ], and pigs [ 12 , 13 ], which are largely due to the alteration in the gastrointestinal microbiota [ 14 ]. Muramidases also have immunomodulatory functions that have been established in livestock [ 15 , 16 ]. MUR hydrolyzes PGN-containing bacteria cell debris, which can improve digestive and absorptive functions and positive alteration of the intestinal inflammatory response, with subsequent enhancements in gut health and broiler performance [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon could be explained by the fact that MUR increases AA absorption in the small intestine by the host, leaving less AA available for bacterial growth in the caecum which may have an impact on bacterial fermentation in the large intestine. In previous studies ( Sais et al, 2020 ; Wang et al, 2021 ; Brugaletta et al, 2022 ), MUR changed the overall cecal bacterial community structure, reducing cecal alpha diversity, and also its taxonomic composition, compared to the control broilers group. Thus, those changes on the cecal microbiome could be interpreted as an indirect or postbiotic effect of MUR, although, Wang et al (2021) also suggested that effects of MUR on the cecal microbiome could be direct.…”
Section: Discussionmentioning
confidence: 71%
“…In previous studies ( Sais et al, 2020 ; Wang et al, 2021 ; Brugaletta et al, 2022 ), MUR changed the overall cecal bacterial community structure, reducing cecal alpha diversity, and also its taxonomic composition, compared to the control broilers group. Thus, those changes on the cecal microbiome could be interpreted as an indirect or postbiotic effect of MUR, although, Wang et al (2021) also suggested that effects of MUR on the cecal microbiome could be direct. In any case, it could be speculated that these changes in the microbiota might also have an impact on microbial fermentation patterns, for instance increasing short chain fatty acid production from NSP.…”
Section: Discussionmentioning
confidence: 71%
“…When taking into consideration that high performing birds tend to have a continuous elevated level of intestinal inflammation, it may be useful to support these negative feedback mechanisms. In line with this strategy, we recently showed that a microbial muramidase added to broiler feed was able to break down peptidoglycan from the intestinal microbiome into muramyl dipeptide, a NOD ligand, thereby dampening down inflammation in the duodenum of broilers ( Wang et al., 2021 ).…”
Section: Intestinal Inflammation and Gut Leakagementioning
confidence: 96%
“…In addition, a population of tissue-resident T-lymphocytes, residing in between the intestinal epithelial cells, the so-called intraepithelial lymphocytes, is considered to play a prominent role in gut health and homeostasis in humans and other mammals ( Olivares-Villagomez and Van Kaer, 2018 ). We recently showed that this population of intraepithelial lymphocytes can be stimulated in the small intestinal mucosa of chickens by adding a peptidoglycan-degrading enzyme to the feed ( Wang et al., 2021 ). The enzymatic degradation of bacterial peptidoglycan has been shown to generate nucleotide-binding oligomerization domain (NOD)-activating muramyl dipeptides.…”
Section: The Immunology Of Gut Healthmentioning
confidence: 99%